Vaccination of pregnant women: an overview of European policies and strategies to promote it - S. Properzi; R. Carestia; V. Birettoni; V. Calesso; B. Marinelli; E. Scapicchi; E. Brillo; C. de Waure (Frontiers in Public Health)
Maternal immunization is a valuable tool for protecting mother and unborn child from vaccine-preventable diseases. However, the implementation of strategies for vaccinating pregnant women has only recently gained traction. This work is aimed at providing an overview of European vaccination strategies and gathering evidence on interventions enhancing vaccination knowledge, attitudes, and behaviors (KAB) in pregnant women. To summarize current pregnancy vaccination strategies in Europe, we consulted literature, institutional national health system websites, and the ECDC Vaccine Scheduler. The review of evidence on interventions targeting pregnant women’s vaccination KAB was performed by searching primary studies on PubMed and Web of Science. The 27 EU member states offer various vaccinations in pregnancy, but only 10 recommend all of these: tetanus, pertussis, diphtheria, influenza, and COVID-19, albeit with different administration schedules. The literature review included 7 studies, 3 from Italy and 4 from other European countries (UK, Netherlands, Greece, Poland, and Ukraine). They were conducted in various settings such as childbirth preparation courses, prenatal visits, and online platforms, and all included educational interventions providing information on vaccine safety and efficacy during pregnancy. Knowledge about vaccines and vaccine-preventable diseases, generally low in the pre-intervention period, increased post-intervention, with a rise in awareness of the risks associated with infectious diseases and the recommended vaccines, a reduction in vaccine-related misinformation, and a greater propensity to vaccinate both newborns and themselves. Furthermore, there was a significant increase in adherence to recommended vaccinations, particularly among those with higher educational levels. However, vaccine hesitancy persisted, influenced by factors such as fear of adverse events and the lack of recommendations from healthcare providers. Variations in pregnancy vaccination strategies across Europe emphasize the importance of establishing a unified framework to optimize maternal and fetal health outcomes through evidence-based policies. Educational interventions may positively impact pregnant women’s KAB, therefore promoting vaccination uptake.